Preliminary notes of the marine fouling at the port of Mar del Plata (Argentina) - Bastida, Ricardo (1967)
Reference is made in this note to the qualitative and quantitative composition of the benthic communities of the Mar del Plata harbour (Argentina). Researchs on the fouling organisms were carried out based in our former studies of the area. This is the first time that fouling studies are being done in our country. Studies in detail of the fouling organisms constitute the present stage of the investigations, and are made over an experimental raft. As at the present time we have only reached up to the 6th month of observations, we are given a preliminary idea of the fouling development. We include the diagrams of the monthly main species frequency. Data of the accumulative panels are excluded.